Determination of major and trace elements in biologica certified reference materials of plant and animal origin by inductively coupled mass-spectrometry - E. V. Smirnova; O. V. Zarubina (Стандартные образцы, 2017)
Abundances of 56 major and trace elements have been determined by ICP-MS for ten reference materials of different composition plants and fish tissues created at the National Institutes of China, Russia, Canada, Poland and Austria. Application of high-resolution instrument ELEMENT 2 allowed any interference to be excluded using the modes of medium and high resolution, sensitivity signal which is sufficient for measuring small and ultra abundances ofmost analytes in study samples. Real detection limits of determined elements were obtained by ICP-MS routine analysis with the autoclave preparation of samples. The obtained СИСП-МС data, complementing the elemental characteristics of RMs may be employed as the indicative values when analyzing biological materials.